Comprehensive evaluation on tailor-made deep eutectic solvents (DESs) in extracting tea saponins from seed pomace of Camellia oleifera Abel. (16th April 2021) - Tang, Yayuan; He, Xuemei; Sun, Jian; Liu, Guoming; Li, Changbao; Li, Li; Sheng, Jinfeng; Zhou, Zhugui; Xin, Ming; Ling, Dongning; Yi, Ping; Zheng, Fengjin; et al.
Highlights: DESs were initially developed as green media for the extraction of tea saponins from C. oleifera seed pomace. The major factors influencing the extraction were optimized by RSM. Eight tea saponins from the C. oleifera seed pomace were identified firstly by UHPLC-HF MS. Proper choice of extraction solvent cannot influence bioactivities of tea saponin. Abstract: Tea saponins from Camellia oleifera Abel. seed pomace are new sources of commercial saponins. This study established an eco-friendly and efficient extraction method for tea saponins from C. oleifera seed pomace. A ternary deep eutectic solvent (DES) composed of l -proline, glycerol and sucrose (4:10:1 in molar ratio, abbreviated as PGS-5) achieved the highest extraction yield of tea saponins among all screened DESs. A maximum extraction yield of 23.22 ± 0.28% was obtained using PGS-5 under the optimized extraction time, DES concentration and liquid-solid ratio. Through ultraviolet, Fourier transform infrared spectroscopy and ultrahigh-performance liquid chromatography-Q Exactive HF mass spectroscopy, as well as analyses of antioxidant and antimicrobial activities, it was determined that extracted saponins did not altered during processing. Therefore, PGS-5 can serve as a solvent to obtain stable and beneficial tea saponins from C. oleifera seed pomace.